Penerapan Outdoor Augmented Reality Berbasis Android Dengan Metode Addie Untuk Meningkatkan Minat Siswa SMA Dalam Pembelajaran Seni Budaya - Ichsanulhaq, Gumilar; Supriatna, Asep (Institut Teknologi Garut, 2025)
This study was motivated by the low level of student interest in Cultural Arts subjects, which was triggered by conventional teaching methods that lacked interactivity. Augmented Reality (AR) is offered as an innovative solution to create an immersive learning experience, especially in outdoor settings that have not been widely explored. Although the effectiveness of AR has been proven in various contexts, its implementation for Cultural Arts learning in real environments is still very limited. Therefore, this research is urgent to fill this gap and provide empirical evidence on the use of AR in increasing student engagement. This study fills this gap by applying an AR application featuring 3D objects, 2D objects, videos, and practice questions using Unity Engine and Vuforia Engine. The development method follows the ADDIE model (Analyze, Design, Development, Implementation, Evaluation), while functionality testing uses Blackbox Alpha and learning interest evaluation uses Beta. The result is an AR Cultural Arts application, as evidenced by Beta testing results using a Likert scale, which produced a score of 4.00 with 35 student respondents in the “High” category stating that the application can increase the learning interest of high school students.